Preparation method of silicon dioxide aerogel with high porosity

By introducing methylalkoxysilane and template agent in the preparation process of silica aerogel, and curing and drying through photoinduced curing and drying, the problem of low porosity of existing aerogels is solved, achieving high porosity and Improved hydrophobic performance, suitable for industrial production and wide application.

CN119461392APending Publication Date: 2025-02-18HUBEI HEYUAN NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411646104.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing silica aerogels have low porosity and are difficult to meet the wide application needs of hydrophobic materials in the fields of waterproofing, moisture-proofing, corrosion-proofing, etc.

Method used

Hydrolysis reaction is carried out by adding silicon source, methylalkoxysilane, silane coupling agent, deionized water, template agent and acid in the solvent, and adding a photoinitiator for ultraviolet irradiation and curing, followed by drying to obtain high Silica aerogel with porosity.

Benefits of technology

It has achieved high porosity (greater than 90%) and good hydrophobic properties (water contact angle greater than 140°), which is suitable for industrial promotion, and has expanded the application scope of materials in waterproofing, moisture-proofing, corrosion-proofing and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461392A_ABST
    Figure CN119461392A_ABST
Patent Text Reader

Abstract

According to the preparation method of the high-porosity silicon dioxide aerogel, a one-pot method is adopted, hydrophobic components are introduced, so that the aerogel has intrinsic hydrophobic performance, application of various scenes can be met, a template agent is introduced and effectively removed in the drying process, and the porosity of the aerogel is improved. The method can complete aerogel preparation in a short time, is high in efficiency and safe and environment-friendly in preparation process, and is suitable for industrial popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aerogel preparation, in particular to a method for preparing high-porosity silicon dioxide aerogel. Background Art

[0002] Silica aerogel (hereinafter referred to as aerogel) has the characteristics of good thermal insulation, low density, low sound transmission rate and large surface area due to its special structure, and has a very broad application prospect. Hydrophobic fumed silica is generally a post-processed product. Different types of gas phase or precipitation silica can be selected as raw materials, and reacted with suitable compounds through silicon hydroxyl groups; this product is hydrophobic due to the surface connection of non-hydrolyzed methyl groups. Compared with hydrophilic materials, hydrophobic silica aerogel has significant waterproof properties. This is because the surface of hydrophobic materials has a lower surface energy, making it difficult for water molecules to adhere and diffuse on its surface. This characteristic makes hydrophobic silica aerogel have a wide range of application prospects in the fields of waterproofing, moisture resistance, and corrosion resistance. For example, in construction projects, hydrophobic silica aerogel can be used as a waterproof material for the construction of walls, roofs and other parts to effectively prevent moisture penetration and leakage. In addition, in the field of electronic appliances, hydrophobic silica aerogel can also be used as a moisture-proof material to protect circuit boards and electronic components to prevent short circuits and damage caused by moisture.

[0003] The preparation method of aerogel mostly adopts the process of hydrolyzing the silicon source (generally methyl orthosilicate, ethyl orthosilicate, water glass) into silanol, then heating it to make it gel, and finally drying it to obtain aerogel. The hydrolyzed silanol is coated on a carrier, and the aerogel composite material such as felt, plate, sheet and blanket is obtained by drying; if it is not coated on a carrier, the aerogel block, particle and powder are obtained by drying. The means of aerogel include microwave, infrared or water bath heating, etc. This process promotes molecular collision, the formation of silicon-oxygen-silicon bonds, increases the gelation rate, strengthens the skeleton, and ensures that the structural collapse caused by capillary action is reduced during drying. The drying methods are freeze drying, atmospheric pressure drying and supercritical drying, among which supercritical drying accounts for the vast majority. The principle of drying is that under a certain pressure and temperature, the fluid medium reaches a supercritical state, thereby taking away the solvent in the pores to achieve the purpose of drying.

[0004] The current process for aerogel is to use microwave heating to make hydrolyzed ethyl orthosilicate or methyl orthosilicate, i.e., silica sol, form gel. This method has a fast gelation speed and can complete gelation in about half an hour, with high efficiency, but due to the use of microwave heating, there are major safety hazards; there are also infrared and water bath heating methods to achieve gelation, but the time is long and the efficiency is low, which is not conducive to industrial production; there is also a method of not heating and shortening the gelation time by increasing the amount of catalyst. Although safety is improved, it is difficult to control the amount of catalyst added in this method because the range of the catalyst addition is very narrow, and it is also necessary to quickly achieve uniform stirring, which is difficult.

[0005] Chinese patent document CN111592004A reports that photoinitiation can quickly complete gelation and produce low thermal conductivity aerogel, but it requires more steps and repeated soaking and cleaning, the preparation cycle is long and the porosity is only 49%. In addition, the important property of aerogel - hydrophobicity - is not mentioned, which limits the application scope of aerogel as a hydrophobic material.

[0006] Therefore, it is necessary to propose a method for preparing high-porosity silica aerogel to solve the defect of low porosity, meet the hydrophobic properties, and expand the application range of the material. Summary of the invention

[0007] The present invention provides a method for preparing a high-porosity silica aerogel, which solves the defect of low porosity of the silica aerogel in the prior art while ensuring hydrophobicity, and expands the application range of the material.

[0008] The technical solution of the present invention is achieved in this way:

[0009] A method for preparing high-porosity silica aerogel, comprising the following steps:

[0010] Adding silicon source, methyl alkoxysilane, silane coupling agent, deionized water, template agent and acid into the solvent, and causing hydrolysis reaction at 20-60°C;

[0011] A photoinitiator is added to the product obtained by the hydrolysis reaction, and the product is cured by ultraviolet light for 0.5 to 30 minutes, and then dried to obtain a high-porosity aerogel.

[0012] Furthermore, the molar ratio of the silicon source, methylalkoxysilane and coupling agent is 1:(0.3-0.6):(0.3-0.6).

[0014] Furthermore, the methylalkoxysilane is selected from one or more of methyltrimethoxysilane, methyltriethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, trimethylmethoxysilane and trimethylethoxysilane.

[0015] Furthermore, the template agent is selected from one or more of hexadecyltrimethylammonium bromide, tetrapropylammonium hydroxide, ethylenediamine, and pyrrolidine.

[0016] Furthermore, the amount of the template agent used is 1-3% of the total mass of the hydrolysis reaction system.

[0017] Furthermore, the ultraviolet light is UVA ultraviolet light with a wavelength of 320-420 nm, such as 324 nm, 365 nm, 395 nm, and 405 nm.

[0018] Furthermore, in the above preparation method:

[0019] The silicon source is selected from one or more of ethyl orthosilicate and methyl orthosilicate;

[0020] The coupling agent is selected from one or more of 3-methacryloxypropyltrimethoxysilane and 3-methacryloxypropyltriethoxysilane;

[0021] The purpose of adding the acid is to provide an acidic hydrolysis environment, and the acid can be selected from one or more of hydrochloric acid, oxalic acid, sulfuric acid, and nitric acid. The preferred concentration is 5-10wt%, and the amount used is 0.02-0.05 times the molar amount of the silicon source; the amount of deionized water used is 4 times the molar amount of the silicon source.

[0022] The solvent is selected from one or more of ethanol, methanol and n-hexane;

[0023] The photoinitiator is selected from one or more of photoinitiators such as 369, 907, 184, 2959, etc.

[0024] Furthermore, the drying process conditions are normal pressure and the drying temperature is 100-250°C.

[0025] The present invention also proposes that the silica aerogel prepared by the above method has a porosity greater than 90%, preferably 91%, 92%, 93%, 94%, 95%, 96%, 97%, or 98%.

[0026] Furthermore, the water contact angle of the silica aerogel is greater than 140°, preferably, the water contact angle is greater than 150°, and more preferably, the water contact angle is greater than 155°, such as 155°, 156°, 157°, 158°.

[0027] Compared with the prior art, the beneficial effects of the present invention include at least:

[0028] The preparation method of the present invention adopts a one-pot method to introduce a hydrophobic component methyl alkoxy silane to make the aerogel have intrinsic hydrophobic properties, which can meet the application of various scenarios. The porosity of the aerogel is improved by introducing a template and effectively removing it during the drying process. The method can complete the preparation of aerogel in a short time, has high efficiency, and the preparation process is safe and environmentally friendly, and is suitable for industrial promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 Schematic diagram of the chemical route for preparing the hydrophobic silica aerogel of the present invention.

[0031] Figure 2 This is a diagram showing the hydrophobicity test effect of the hydrophobic silica aerogel described in the present invention. DETAILED DESCRIPTION

[0032] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] In one embodiment, a method for preparing a high-porosity silica aerogel is provided, comprising the steps of:

[0034] S1. Add a silicon source, methyl alkoxysilane, a silane coupling agent, deionized water, a template agent and an acid into a solvent, and a hydrolysis reaction occurs at 20 to 60°C;

[0035] The molar ratio of the silicon source, methyl alkoxy silane and coupling agent is 1: (0.3-0.6): (0.3-0.6);

[0036] The methylalkoxysilane is selected from one or more of methyltrimethoxysilane, methyltriethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, trimethylmethoxysilane, and trimethylethoxysilane; the template is selected from one or more of hexadecyltrimethylammonium bromide, tetrapropylammonium hydroxide, ethylenediamine, and pyrrolidine; the amount of the template is 1-3% of the total mass of the hydrolysis reaction system;

[0037] S2. Add a photoinitiator to the product obtained by the hydrolysis reaction, pour it into a mold, cure it by UVA ultraviolet light irradiation for 0.5 to 30 minutes, soak it in a solvent for 10-30 minutes, dry it and remove the template to obtain a high-porosity aerogel.

[0038] In the above embodiment, the scheme adopts a one-pot method to introduce hydrophobic components to make the aerogel have intrinsic hydrophobic properties, which can meet the application of various scenarios. The porosity of the aerogel is improved by introducing a template and effectively removing it during the drying process. This method can complete the preparation of aerogel in a short time, with short time, high efficiency, and safe and environmentally friendly preparation process, which is suitable for industrial promotion.

[0039] In a preferred embodiment, the silicon source is selected from one or more of ethyl orthosilicate and methyl orthosilicate; the coupling agent is selected from one or more of 3-methacryloxypropyltrimethoxysilane and 3-methacryloxypropyltriethoxysilane.

[0040] Taking the reaction of ethyl orthosilicate, methyl triethoxysilane, and 3-methacryloxypropyl triethoxysilane as an example, the general reaction formula of the above aerogel preparation process is as follows: Figure 1 As shown. The final prepared silica aerogel material has a typical porous material structure under SEM electron microscope. The porosity of silica aerogel is greater than 90%, preferably greater than 98%; the hydrophobic performance test is as shown Figure 2 As shown, the water contact angle is characterized by being greater than 150°, preferably greater than 152°, and more preferably greater than 158°.

[0041] In some embodiments, the purpose of adding the acid is to provide an acidic hydrolysis environment, and the acid can be selected from one or more of hydrochloric acid, oxalic acid, sulfuric acid, and nitric acid. The preferred concentration is 5-10wt%, and the amount used is 0.02-0.05 times the molar amount of the silicon source; the amount of deionized water used is 4 times the molar amount of the silicon source.

[0042] In a preferred embodiment, the solvent is selected from one or more of ethanol, methanol, and n-hexane; the photoinitiator is selected from one or more of photoinitiators such as 369, 907, 184, 2959, etc.; the ultraviolet light is UVA ultraviolet light with a wavelength of 320 to 420 nm, such as 324 nm, 365 nm, 395 nm, and 405 nm.

[0043] In a preferred embodiment, the drying process condition is normal pressure, and different drying temperatures are set for different templates. The purpose is to remove excess moisture on the one hand, and to promote volatilization or thermal decomposition of the template to generate pores on the other hand; preferably, the drying temperature is selected to be 100-250°C, which is specifically set according to the relevant physical and chemical properties of the template.

[0044] Example 1

[0045] TES, methyl triethoxysilane, 3-methacryloxypropyl triethoxysilane, ethanol, water, 5wt% hydrochloric acid, and photoinitiator 369 were sequentially put into a three-necked flask with stirring and water bath heating according to the molar ratio of 1:0.3:0.3:10.6:4:0.02:0.03, and then 1% of the total mass of the solution was added with ethylenediamine, the temperature was controlled at 50°C, the reaction was performed for 1.5 hours, and the mixture was poured into a mold, and then irradiated with an ultraviolet lamp with a wavelength of 395nm, and almost no ethanol gas was detected during the whole process. After the gel was allowed to gel for 10 minutes, it was immersed in n-hexane for 3 hours, and then dried in an oven at 150°C for 3 hours to obtain a pure hydrophobic aerogel.

[0046] Example 2

[0047] TES, methyl triethoxysilane, 3-methacryloxypropyl triethoxysilane, n-hexane, water, 5wt% hydrochloric acid, and photoinitiator 907 were sequentially put into a three-necked flask with stirring and water bath heating according to the molar ratio of 1:0.4:0.4:9:4:0.03:0.04, and then 2% of the total mass of the solution was added with ethylenediamine, the temperature was controlled at 50°C, the reaction was performed for 1.5 hours, and the solution was poured into a mold, and then irradiated with a UV lamp with a wavelength of 365nm. After 20 minutes, the gel was formed, and almost no ethanol gas was detected during the whole process. The gel was then soaked in n-hexane for 3 hours, and then dried in an oven at 150°C for 3 hours to obtain a pure hydrophobic aerogel.

[0048] Example 3

[0049] Methyl orthosilicate, methyl trimethoxysilane, 3-methacryloxypropyl trimethoxysilane, methanol, water, 5wt% hydrochloric acid, and photoinitiator 184 were sequentially placed in a three-necked flask with stirring and water bath heating according to a molar ratio of 1:0.5:0.6:8.6:4:0.05:0.08, and then 1.5% of the total mass of the solution was added with hexadecyl trimethyl ammonium bromide, the temperature was controlled at 30°C, the reaction was performed for 2.5 hours, and the mixture was poured into a mold, and then irradiated with an ultraviolet lamp with a wavelength of 405nm. After 5 minutes, the gel was formed, and almost no ethanol gas was detected during the whole process. The gel was then immersed in n-hexane for 3 hours and dried in an oven at 250°C for 2 hours to obtain a hydrophobic aerogel.

[0050] Example 4

[0051] Methyl orthosilicate, methyl trimethoxysilane, 3-methacryloxypropyl trimethoxysilane, methanol, water, hydrochloric acid, and photoinitiator 369 were sequentially put into a three-necked flask with stirring and water bath heating according to the molar ratio of 1:0.5:0.6:8.6:4:0.05:0.08, and then 1.5% of the total mass of the solution was added with hexadecyl trimethyl ammonium bromide, the temperature was controlled at 30°C, the reaction was carried out for 2.5 hours, and the mixture was poured onto a ceramic fiber felt substrate, and then irradiated with an ultraviolet lamp with a wavelength of 405nm. After 5 minutes, the gel was formed, and almost no ethanol gas was detected during the whole process. The gelled felt was dried in an oven at 250°C for 2 hours to obtain a hydrophobic aerogel felt.

[0052] Comparative Example 1

[0053] The preparation method of the hydrophobic aerogel is the same as that of Example 1, except that no template is added.

[0054] Comparative Example 2

[0055] The preparation method of the hydrophobic aerogel is the same as that of Example 1, except that the amount of the template added is 5%.

[0056] Comparative Example 3

[0057] The preparation method of the aerogel is the same as that of Example 1, except that methyltriethoxysilane is not added.

[0058] The parameters of the aerogels obtained in the above examples and comparative examples were tested, including density, porosity, hydrophobicity and thermal conductivity. The test results are shown in Table 1.

[0059] Table 1: Performance test results

[0060] performance Density kg / m3 Porosity % Water contact angle° Thermal conductivity W / m·℃ Example 1 39.6 98.2 157.1 0.016 Example 2 39.3 98.4 157.6 0.015 Example 3 39.1 98.5 157.9 0.015 Example 4 213.5 90.3 152.4 0.018 Comparative Example 1 527.1 48.1 / / Comparative Example 2 / 73.8 / / Comparative Example 3 / 83.1 89.3 /

[0061] It can be seen from the above Examples 1-3 that the porosity of the prepared silica aerogel is much higher than that of the prior art, and its water contact angle test shows better hydrophobicity, meeting the performance requirements as a hydrophobic material. Example 4 Due to the presence of the substrate ceramic fiber felt, the porosity is not as high as that of the pure aerogel in Example 1, but it can still meet the performance requirements. The porosity decreases when no template is added in Comparative Example 1 and when the amount of template added in Comparative Example 2 is too large. When methyltriethoxysilane is not added in Comparative Example 3, the hydrophobicity decreases significantly, and the porosity also decreases significantly, indicating that the use of methyltriethoxysilane synergistically improves the hydrophobicity and porosity.

[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing high-porosity silica aerogel, characterized in that the steps include: Adding silicon source, methyl alkoxysilane, silane coupling agent, deionized water, template agent and acid into the solvent, and causing hydrolysis reaction at 20-60°C; A photoinitiator is added to the product obtained by the hydrolysis reaction, and the product is cured by ultraviolet light for 0.5 to 30 minutes, and then dried to obtain a high-porosity aerogel.

2. The preparation method according to claim 1, characterized in that The molar ratio of the silicon source, methyl alkoxy silane and coupling agent is 1:(0.3-0.6):(0.3-0.6).

3. The preparation method according to claim 1, characterized in that: The methylalkoxysilane is selected from one or more of methyltrimethoxysilane, methyltriethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, trimethylmethoxysilane and trimethylethoxysilane.

4. The preparation method according to claim 1, characterized in that: The template agent is selected from one or more of hexadecyltrimethylammonium bromide, tetrapropylammonium hydroxide, ethylenediamine and pyrrolidine.

5. The preparation method according to claim 4, characterized in that: The amount of the template agent used is 1-3% of the total mass of the hydrolysis reaction system.

6. The preparation method according to claim 1, characterized in that: The ultraviolet light is UVA ultraviolet light.

7. The preparation method according to claim 1, characterized in that: The silicon source is selected from one or more of ethyl orthosilicate and methyl orthosilicate; And / or, the coupling agent is selected from one or more of 3-methacryloxypropyltrimethoxysilane and 3-methacryloxypropyltriethoxysilane; And / or, the acid is selected from one or more of hydrochloric acid, oxalic acid, sulfuric acid and nitric acid; And / or, the solvent is selected from one or more of ethanol, methanol, and n-hexane; And / or, the photoinitiator is selected from one or more of 369, 907, 184, and 2959.

8. The preparation method according to claim 1, characterized in that: The drying process conditions are normal pressure and the drying temperature is 100-250°C.

9. The silica aerogel prepared by the method according to any one of claims 1 to 8, characterized in that: The porosity of the silica aerogel is greater than 90%.

10. The silica aerogel according to claim 9, characterized in that The water contact angle of the silica aerogel is greater than 140°.

Citation Information

Patent Citations

  • Preparation method of silicon dioxide aerogel, and silicon dioxide aerogel

    CN111592004A